The association between SDGs knowledge and sustainability behaviour of higher institution students / Nur Fadhlina Zainal Abedin ... [et al.] - Zainal Abedin, Nur Fadhlina; Yaakob, Hafisah; Ibrahim, Siti Sara; Mohd Shariff, Sharfizie (2021)
The Sustainable Development Goals (SDGs) established in 2015 includes 17 goals with 169 targets and 232 specific indicators that have previously called for a deep transformation of human, social, and environmental development objectives (Moyer & Hedden, 2020; Griggs et al., 2013, UNGA, 2015). These goals represent an ambitious global action plan to respond to major global challenges such as poverty, social exclusion, and environmental degradation, and to achieve sustainable development for all by 2030 (Pineda-Escobar, 2019). Therefore, complementary actions by governments especially Higher Education Institutions (HEIs), are required to ensure the achievement of SDG objectives towards its 2030 Agenda for Sustainable Development. Responding to this issue, this study is empirically done to examine the association between SDGs Knowledge and Sustainability Behaviour among students in the Higher education setting. It is hoped that this study would be able to indicate the level of knowledge towards SDGs agenda in higher education institutions that may influence the behaviour towards sustainability practices. This study is critically important to assist the university’s strategic plan in line with the sustainability agenda to support the national inspiration towards the achievement of the 2030 Agenda for Sustainable Development.